answer:

Subject Math

What affects the change of values of the function?

answer

From the given values of x, substituting the numbers to each function will prove and support the answer to be stated. There are different functions to substitute the 3 values for each functions. Determining the values as (a) f(-3), (b) f(1), and (c) f(4) in each of the following functions, the values of f(x) as x increases would be:

a. f(x) = 2x

Let x= -3, f(-3) = 2(-3) , therefore ,the value of f(x) at x =-3 is -6.

Let x=1, f(1) = 2(1) , therefore ,the value of f(x) at x = 1 is 2

Let x=4, f(4) = 2(4) , therefore ,the value of f(x) at x = 4 is 8.

Finally,from the above result, the value of f(x) in the function f(x) = 2x increases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

b. f(x) = 2x + 1

Let x= -3, f(-3) = 2(-3) + 1 , therefore ,the value of f(x) at x = -3 is -5.

Let x=1, f(1) = 2(1) + 1 , therefore ,the value of f(x) at x = 1 is 3.

Let x=4, f(4) = 2(4) + 1, therefore ,the value of f(x) at x = 4 is 9.

Finally,from the above result, the value of f(x) in the function f(x) = 2x + 1 increases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

c. f(x) = -3x

Let x= -3, f(-3) = -3(-3) , therefore ,the value of f(x) at x = -3 is 9.

Let x=1, f(1) = -3(1), therefore ,the value of f(x) at x = 1 is -3.

Let x=4, f(4) = -3(4), therefore ,the value of f(x) at x = 4 is -12.

Finally,from the above result, the value of f(x) in the function f(x) = -3x decreases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

d. f(x) = -3x – 4

Let x= -3, f(-3) = -3(-3) -4 , therefore ,the value of f(x) at x = -3 is 5.

Let x=1, f(1) = -3(1) - 4, therefore ,the value of f(x) at x = 1 is -7.

Let x=4, f(4) = -3(4) -4 , therefore ,the value of f(x) at x = 4 is -16.

Finally,from the above result, the value of f(x) in the function f(x) = -3x - 4 decreases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

e. f(x) = 2 – 3x

Let x= -3, f(-3) =2-3(-3), therefore ,the value of f(x) at x = -3 is 11.

Let x=1, f(1) = 2-3(1), therefore ,the value of f(x) at x = 1 is -1.

Let x=4, f(4) = 2-3(4) , therefore ,the value of f(x) at x = 4 is -9.

Finally,from the above result, the value of f(x) in the function f(x) = 2 -3x decreases as x increases.

Change of values of the function is dependent on the dependent variables given as (a) f(-3), (b) f(1), and (c) f(4).

Step-by-step explanation: